2008
DOI: 10.1016/j.str.2008.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Defining Molecular and Domain Boundaries in the Bacteriophage ϕ29 DNA Packaging Motor

Abstract: SUMMARY Cryo-electron microscopy (cryoEM) studies of the bacteriophage ϕ29 DNA packaging motor have delineated the relative positions and molecular boundaries of the 12-fold symmetric head-tail connector, the 5-fold symmetric prohead RNA (pRNA), the ATPase that provides the energy for packaging, and the procapsid. Reconstructions, assuming 5-fold symmetry, were determined for proheads with 174-base, 120-base, 71-base pRNA, proheads lacking pRNA; proheads with ATPase bound, and proheads in which the packaging m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
149
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(157 citation statements)
references
References 42 publications
(51 reference statements)
8
149
0
Order By: Relevance
“…Earlier cryo-EM studies (3, 21) reported a contact, and our new structural model of pRNA defines this interaction. gp8 subunits abutting the connector adopt a conformation distinct from subunits in the rest of the prohead in that the BIG2 surface domains are rotated 180°away from the connector (3,21). These five unique gp8 surfaces at the capsid portal vertex appear to form specific, symmetric contacts with a minor groove-facing dinucleotide stack (G 55 and A 56 ) in the L E loop of the five pRNA protomers.…”
Section: Two Flexible Joints and Lack Of Tertiary Interactions In Thementioning
confidence: 99%
See 4 more Smart Citations
“…Earlier cryo-EM studies (3, 21) reported a contact, and our new structural model of pRNA defines this interaction. gp8 subunits abutting the connector adopt a conformation distinct from subunits in the rest of the prohead in that the BIG2 surface domains are rotated 180°away from the connector (3,21). These five unique gp8 surfaces at the capsid portal vertex appear to form specific, symmetric contacts with a minor groove-facing dinucleotide stack (G 55 and A 56 ) in the L E loop of the five pRNA protomers.…”
Section: Two Flexible Joints and Lack Of Tertiary Interactions In Thementioning
confidence: 99%
“…The requirement of a RNA-ring structure in the assembly and function of the ϕ29 DNA packaging motor contrasts with equivalent motors in other dsDNA phages such as T4, SPP1, lambda, and P22 where protein-protein contacts anchor ring ATPases to the phage proheads (1). Cryoelectron microscopy (cryo-EM) 3D reconstructions (2,3,8) show that pRNA is strategically positioned in the ϕ29 packaging motor to link the capsid, connector and ATPase components of the motor (Fig. 1A).…”
mentioning
confidence: 99%
See 3 more Smart Citations